Clinico Pathological and Ultrasonographic Evaluation of Dogs with Ascites - Tyagi, Milind; katoch, Ajay; Sharma, Ankur; Sharma, Pardeep; Kumar, Adarsh (Indian Journal of Veterinary Medicine, 2025)
Ascites is a common clinical manifestation of underlying hepatic pathology in dogs, often resulting from portal hypertension, cirrhosis, or hypoalbuminemia. The study was aimed to evaluate haematological, biochemical, electrolyte, ascitic fluid, and ultrasonographic alterations in 15 dogs with ascites. Haematologically mean values of Hb, PCV and TEC were significantly reduced while total leukocyte with neutrophil count were significantly increased. Biochemically, mean values of total protein and albumin were significantly reduced while mean values of ALT, AST, ALP, and BUN were significantly increased. On sonography increased parenchymal echogenicity, irregular liver margins, rounding of liver margins and diffuse nodular changes were noticed.